2012
DOI: 10.1371/journal.pone.0042332
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 1950-MHz TD-SCDMA Electromagnetic Fields Affects the Apoptosis of Astrocytes via Caspase-3-Dependent Pathway

Abstract: The usage of mobile phone increases globally. However, there is still a paucity of data about the impact of electromagnetic fields (EMF) on human health. This study investigated whether EMF radiation would alter the biology of glial cells and act as a tumor-promoting agent. We exposed rat astrocytes and C6 glioma cells to 1950-MHz TD-SCDMA for 12, 24 and 48 h respectively, and found that EMF exposure had differential effects on rat astroctyes and C6 glioma cells. A 48 h of exposure damaged the mitochondria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 34 publications
3
49
0
2
Order By: Relevance
“…2c, d). To further confirm these findings, we detected the protein expression and activity of Caspase-3, which have been previously demonstrated as apoptosis indicators and are also widely used for apoptosis detection229. The protein expression of total and cleaved Caspase-3, the active form of Caspase-3, was not changed after a 4 W/kg RF-EMF exposure for 3 days (Fig.…”
Section: Resultssupporting
confidence: 65%
“…2c, d). To further confirm these findings, we detected the protein expression and activity of Caspase-3, which have been previously demonstrated as apoptosis indicators and are also widely used for apoptosis detection229. The protein expression of total and cleaved Caspase-3, the active form of Caspase-3, was not changed after a 4 W/kg RF-EMF exposure for 3 days (Fig.…”
Section: Resultssupporting
confidence: 65%
“…No change in the mRNA expression of apoptosis-related genes Bax and Bcl-2 after RF-EMF exposure was inspected [35]. In contrast, a previous study has reported that 1950-MHz RF-EMF exposure may cause transcriptional changes in apoptosis related genes, such as Bax [36]. Also the up-regulation of apoptosis-related genes have also been previously observed in embryonic stem cell derived neural progenitor cells in vitro [19].…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system (CNS) is a main concern with regards to the effects of RF-EMF, since mobile phone use involves close exposure or immediate contact with the head1. The biological effects of RF-EMF exposure on human health remain unclear because of conflicting findings of various studies23.…”
mentioning
confidence: 99%
“…Cellular effects of RF-EMF exposure reportedly involve the apoptotic pathway, extracellular signal pathway, DNA damage response, cell proliferation, and cell cycle312131415. The effect of EMF exposure on autophagy in mammalian cells has been documented1617.…”
mentioning
confidence: 99%